2011
DOI: 10.1590/s0037-86822011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da tuberculose multidroga resistente durante a gravidez, em Campinas, Estado de São Paulo, Brasil, no período de 1995 a 2007

Abstract: RESUMOIntrodução: Foi feito um acompanhamento das gestantes tratadas para tuberculose multidroga resistente (TB-MDR) durante a gravidez, em Campinas, Estado de São Paulo, no período de 1995 a 2007. Métodos: No estudo retrospectivo, foram incluídas pacientes com cepa resistente, pelo menos à isoniazida e à rifampicina e gravidez em qualquer momento, durante o tratamento. Os casos receberam esquema individualizado baseado nos padrões de resistência medicamentosa e nos antecedentes de tratamento de cada paciente.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In the MDR cases, the second line drugs, including drugs of the amino glycosides group, fluoroquinolone, thioamides, cycloserines, and terizidone, were used in combination with effective first line drugs, and the treatment regime depended on the drug resistance situation of the individual cases [36],[37],[43],[44]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the MDR cases, the second line drugs, including drugs of the amino glycosides group, fluoroquinolone, thioamides, cycloserines, and terizidone, were used in combination with effective first line drugs, and the treatment regime depended on the drug resistance situation of the individual cases [36],[37],[43],[44]. …”
Section: Resultsmentioning
confidence: 99%
“…Regarding effectiveness and safety of anti-TB drugs, results of the reviewed studies showed no significant association between child abnormality and mother’s exposure to anti-TB drugs, both for 1 st and 2 nd line anti-TB drugs during pregnancy [14],[15],[37],[43],[44]. Other significant adverse effects were recorded in a very small number of pregnant women (2 cases of drug induced hepatitis, 2 of PZA allergy, 2 of sensorineural deafness, and 1 of severe nausea and jaundice) and led to termination of therapy without mortality [24],[44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our electronic database searches identified 487 records. After removal of duplicates, excluding studies by title and abstract screening and full-text review (eTable 5 in the Supplement), 10 studies [14][15][16][17][18][19][20][21][22][23] were included in the meta-analysis, which included 288 pregnant patients with MDR-TB (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%